Relationship Between Arm Span Measurements and Body Height in Berane - Milena Mitrovic (Journal of Anthropology of Sport and Physical Education, 2018)
The aim of this study was to determine whether the arm span predicted body height. The sample of respondents was 89 adolescents from Berane, 52 boys and 37 girls. The boy’s average was 17.96 years, and the girl was 18.08 years. After measuring the height and arm span, the central and dispersive parameters for both variables are calculated. The average height of the boys is 182.85±6.55cm and the arm span is 181.04±6.20cm. The average height of the girls is 169.23±9.89cm and the arm span is 167.48±6.39cm. The ratio of body height and arm span was determined by correlation coeffi cients with a confi dence level of 95%. In the end, regression analysis showed whether the arm span predicted body height. The results showed high coeffi cients of correlation and a large percentage of explained variability, which means that the arm span reliably predicts the height of the body.